Eight new species of lichenized Basidiomycota in the genera Acantholichen, Cyphellostereum and Dictyonema s.str. (Agaricales, Hygrophoraceae) from northern South America - Marcano, Vicente (Phytotaxa, 2022)
A study of Acantholichen P.M. Jørgensen, Cyphellostereum D.A. Reid and Dictyonema s.str. C. Agardh ex Kunth from the Venezuelan Andes (Sierra Nevada de Mérida) and the Guayana Highlands (Alto Orinoco) revealed the presence of eight species new to science, viz., Acantholichen dendroideus V. Marcano, Cyphellostereum mucuyense V. Marcano, Dictyonema andinum V. Marcano, D. duidense V. Marcano, D. laurae V. Marcano, D. subinvolutum V. Marcano, D. subsericeum V. Marcano and D. umbricola V. Marcano. Acantholichen dendroideus grows on mosses in shady and humid disturbed forest and is characterized by densely and dichotomously branched microsquamules, with a pruinose surface and large acanthohyphidia. Cyphellostereum mucuyense grows on mosses and sandy soils, lacks a jigsaw-puzzle-shaped hyphal sheath and prothallus, the fibrils are not penetrated by tubular fungal hyphae and the basidiocarp surface is finely arachnoid. This is the first record of Cyphellostereum in Venezuela. Dictyonema andinum might be confused with D. irrigatum (Berkeley & M. A. Curtis) Lücking from the Andaman Islands, but differs in the broader and ascending fibrils, a thicker photobiont layer and hypothallus, as well as the formation of stereoid-corticioid hymenophores. Dictyonema duidense from the Guayana Highlands and D. subsericeum from the Venezuelan Andes belong in the group of shelf-like morphotypes, with a semicircular thallus resembling D. sericeum s.str. Dictyonema duidense grows on tree trunks and is characterized by thick, very broad lobes and an areolate, rugose surface and it lacks clamp connections whereas D. subsericeum grows on tree branches and is characterized by variability of color (white, greenish blue, brown), size and shape (semicircular to hemispherical), filamentous lobes, a hirsute surface, fibrillose margins, clamp connections on the hyphae, cyphelloid hymenophores resembling attachment hapters, and very small, globose to subglobose basidiospores. Dictyonema laurae resembles D. subsericeum but is characterized by a continuous greenish blue crust-like thallus with an irregular surface, with discontinuous, fibrillose, and narrow margins projecting and ascending from the substrate, a hapteriform hymenophore, and its lacks clamp connections on the hyphae. Dictyonema subinvolutum is characterized by a jigsaw-puzzle-shaped hyphal sheath, fibrils penetrated by tubular fungal hyphae, and a smooth, pruinose, resupinate hymenophore. Finally, D. umbricola grows on mosses in very shady habitats and produces a corticioid hymenophore raised from the thallus, resembling apothecial discs, jigsaw-puzzle-shaped cells around the filaments and a distinct, discontinuous, white prothallus. Of the eight species of Dictyonema s.lat. registered from Venezuela, seven are known only from the Venezuelan Andes (A. dendroideus, C. mucuyense, D. andinum, D. laurae, D. subsericeum, D. subinvolutum, D. umbricola) and one is known only from the Venezuelan Amazonas (D. duidense). The high concentration of Acantholichen, Cyphellostereum and Dictyonema species in tropical America and especially of the latter genus in the Venezuelan Andes indicates that this region constitutes an important centre for speciation and endemism of Dictyonema clade/subtribe Dictyonematinae.